2016
DOI: 10.1177/1931243116647770
|View full text |Cite
|
Sign up to set email alerts
|

The Women’s Olympics? A Gender Analysis of NBC’s Coverage of the 2012 London Summer Games

Abstract: This study examines NBC's U.S. prime-time broadcast coverage of the 2012 summer Olympic games for gender equality and compares that coverage to previous years. Olympic coverage is particularly important to female athletes because many receive little media attention beyond Olympic competition. The study found that, for the first time since 1996, NBC gave more airtime to women's sports than to men's sports. However, most of that coverage devoted to women's events was confined to ''socially acceptable'' sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 25 publications
(47 reference statements)
3
40
0
1
Order By: Relevance
“…15,18 A study carried out in the United Kingdom analyzed the television coverage of the events in which there was participation of women and identified that these were mainly composed of sports considered feminine, like gymnastics. 1 Nonetheless, it is observed that the Brazilian media analyzed in this research highlighted the performance of athletes practicing sports perceived as masculine, for example, judo and soccer. It is possible to affirm that this question can be related to the soccer culture characteristic of Brazilians.…”
Section: /14mentioning
confidence: 82%
See 1 more Smart Citation
“…15,18 A study carried out in the United Kingdom analyzed the television coverage of the events in which there was participation of women and identified that these were mainly composed of sports considered feminine, like gymnastics. 1 Nonetheless, it is observed that the Brazilian media analyzed in this research highlighted the performance of athletes practicing sports perceived as masculine, for example, judo and soccer. It is possible to affirm that this question can be related to the soccer culture characteristic of Brazilians.…”
Section: /14mentioning
confidence: 82%
“…Thus, in addition to the greater inclusion of women in the event, it was also possible to perceive the emphasis given by the international media coverage of these athletes. 1 Although in the current scenario the participation of women in Olympic events has gained greater visibility, it cannot be said that male and female athletes have the same opportunities. Sports is a space of production of generalized bodies due to the cultural construction that determines masculinity and femininity representations.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it more difficult to break traditional gender barriers allowing women to participate in masculine sports and men to participate in feminine sports. In fact, many female athletes are only accepted by society and receive coverage in the media if they participate in traditionally feminine sports (Coche and Tuggle 2016). Thus, although ostensibly Amy's message appears to be empowering and inspirational to other females who might find themselves in the position of being a minority in a particular sport, it denies the social, structural and policy changes that are needed to increase opportunities to girls and women and situates the battle for access and acceptance at the level of the individual.…”
Section: Give Sport a Gomentioning
confidence: 99%
“…After all, numerous sports scholars have found the amount of coverage of men's and women's sports during the Olympics tends to be more equitable than during non-Olympic time frames. For example, according to one study, during the 2012 Olympics, the U.S. televised broadcast coverage of women's sports exceeded the coverage of men's (Coche & Tuggle, 2016). Given this, the sexist commentary and coverage seemed out of place.…”
Section: Why Now Is the Time For A Publicmentioning
confidence: 99%